Effectiveness of the Free Nutritious Meal (MBG) Program Policy on Improving Students' Health Quality and Learning Productivity - Andi Sri Adinda; Nursuciyani Jamal (Manunggal Halim Jaya, 2026)
Chronic nutritional problems in Indonesia, such as malnutrition, remain a significant issue requiring continuous attention. The government has launched the Free Nutritious Meals (MBG) program as a strategic nutritional intervention policy, targeting school children, toddlers, and pregnant women. This program is based on the understanding that adequate nutritional intake plays a crucial role in improving health quality and supporting students' learning productivity. This study aims to determine the effectiveness of the Free Nutritious Meals (MBG) program policy in improving the health quality and learning productivity of students. This research uses a qualitative method, with a case study approach, and data collection techniques include interviews, observation, and documentation. Data analysis uses a thematic method. Informants in this study were students, teachers, and parents of students, selected using a purposive sampling technique. The results show that the Free Nutritious Meals (MBG) program has relatively high effectiveness in improving immunity, concentration, and memory. Students are more energetic and fit, which will have a positive impact on enthusiasm, motivation for student attendance, enthusiasm, and active participation in the learning process. Thus, it can improve nutritional status, health quality, and education. This research contributes to the health field by finding that the Free Nutritious Meals (MBG) program is effective as a long-term strategy to improve health and education quality.